A new multiscale modeling framework for investigating thermally-induced flow maldistribution in multi-stream plate-fin heat exchangers. (December 2021) - Niroomand, R.; Saidi, M.H.; Hannani, S.K.
Highlights: A new modeling framework is developed considering thermally-induced maldistribution. Optimum layer arrangement is obtained for a two-phase six-stream plate-fin HE. The effect of heat leakage on thermally-induced maldistribution is evaluated. Some modifications are evaluated to reduce thermally-induced maldistribution. Affected region by thermally-induced flow in the height direction is shown. Abstract: Multi-stream Plate-fin heat exchangers (MSPFHEs) are among the most efficient heat exchangers in energy-based industries. They should be carefully designed to have maximum effectiveness and to avoid wasting energy. Flow maldistribution could significantly degrade the performance of heat exchangers. This study presents a novel modeling framework to capture the thermally-induced maldistribution in two-phase MSPFHEs. The developed model is used to show how thermally-induced flow maldistribution affects the performance of the heat exchanger, and some possible modifications are investigated to reduce its consequences. Our case study results show that thermally-induced maldistribution decreases the total heat transfer by 10.8%. Heat leakage helps to induce less flow near the leakage region, so it can be managed to overcome the initial thermally-induced flow. Moreover, thermally-induced maldistribution affects a limited region along the heat exchanger height direction. So, thermal performance deterioration decreases with increasing the number of layers for each stream. Nevertheless, increasing the heat exchanger length increases the degraded region in the heat exchanger. Thus, increasing the core length is not a good way to counteract the thermal performance deterioration caused by thermally-induced maldistribution. It is also found that an optimum layer arrangement could help to eliminate the thermally-induced maldistribution in the heat exchanger.